Comparative analysis of public opinion for the acceptance of nuclear energy use in Mongolia - S, Odmaa; S, Davaa; G, Nyamdulam; G, Manlaijav (Scientific transaction of the National University of Mongolia. Physics, 2022)
The Mongolian government has a policy to opt a nuclear power as one of the sources of energy in the future. Analysis of public opinion based on the standard survey questionnaire to identify the general public attitude towards nuclear energy use in Mongolia was conducted for the first time in Mongolia in 2011 and for the second time in 2015 for the purpose of further tendency redefining of the public acceptance. The objective of the present paper was to compare the results of the surveys held in 2011 and 2015, and to discuss the alteration and/or the same status in public attitude to nuclear energy use in Mongolia. Based on the results, the main and contributing factors influencing the public opinion for the acceptance of nuclear energy use in Mongolia and the possible reasons forming the public attitude were determined. The results show that Mongolian public opinion on the nuclear energy benefits is likely to be more positive, reasoned mainly by some inevitable factors. PACS number: 01.75.+m, 01.78.+p